Feedback of aggregate patient-reported outcomes (PROs) data to clinicians and hospital end users: findings from an Australian codesign workshop process. Issue 7 (1st July 2022) - Ryan, Olivia Francis; Hancock, Shaun L; Marion, Violet; Kelly, Paulette; Kilkenny, Monique F; Clissold, Benjamin; Gunzburg, Penina; Cooke, Shae; Guy, Lauren; Sanders, Lauren; Breen, Sibilah; Cadilhac, Dominique A
Abstract : Objectives: Patient-reported outcomes (PROs) are increasingly used to measure the patient's perspective of their outcomes following healthcare interventions. The aim of this study was to determine the preferred formats for reporting service-level PROs data to clinicians, researchers and managers to support greater utility of these data to improve healthcare and patient outcomes. Setting: Healthcare professionals receiving PRO data feedback at the health service level. Participants: An interdisciplinary Project Working Group comprised of clinicians participated in three workshops to codesign reporting templates of summarised PRO data (modified Rankin Scale, EuroQol Five Dimension Descriptive System, EuroQol Visual Analogue Scale and Hospital Anxiety and Depression Scale) using a modified Delphi process. An electronic survey was then distributed to short list the preferred templates among a broad sample of clinical end users. A final workshop was undertaken with the Project Working Group to review results and reach consensus on the final templates. Primary and secondary outcome measures: The recommendation of preferred PRO summary data feedback templates and guiding principles for reporting aggregate PRO data to clinicians was the primary outcome. A secondary outcome was the identification of perceived barriers and enablers to the use of PRO data in hospitals. For each outcome measure, quantitative and qualitative data were summarised. Results: 31 Working Group members (19 stroke, 2 psychology, 1 pharmacy, 9 researchers) participated in the workshops, where 25/55 templates were shortlisted for wider assessment. The survey was completed by 114 end users. Strongest preferences were identified for bar charts (37/82 votes, 45%) and stacked bar charts (37/91 votes, 41%). At the final workshop, recommendations to enhance communication of PROs data for comparing health service performance were made including tailoring feedback to professional roles and use of case-mix adjustment to ensure fair comparisons. Conclusions: Our research provides guidance on PROs reporting for optimising data interpretation and comparing hospital performance.